Universal Declaration of Human Rights: An inspirational charter - Marsili, M. (Book of Abstracts of the Fourth Edition of the Unequal World Conference, 2023)
The Universal Declaration of Human Rights (UDHR), proclaimed by the UN Assembly on December 10, 1948, is a touchstone and an inspiration for similar instruments. The European Convention on Human Rights (ECHR), drafted by the Council of Europe in 1950, is considered the European response to the UDHR. The African (Banjul) Charter on Human and Peoples' Rights (ACHP), adopted by the Organisation of African Unity (OAU) in 1981, mirrors the UDHR. The Cairo Declaration on Human Rights in Islam (CDHRI), adopted by the Organisation of the Islamic Conference (OIC) in 1990, which follows the first Muslim instrument, the Universal Islamic declaration of human rights, adopted by the Islamic Council in 1981, can be considered the Islamic version of the UDHR. The Arab Charter on Human Rights(ACHR) adopted by the League of Arab States in 2004, embodies the principles enshrined in the UDHR. In 2012, ten Asian states, members of the Association of Southeast Asian Nations (ASEAN), adopted the ASEAN Human Rights Declaration (AHRD), which in its preamble recalls the UDHR. Despite references and similarities with the UDHR these instruments show limits related to religious constrains—the Islamic Shariah—that do not ensure the full implementation of fundamental human rights. Indeed, some charters are incompatible with international norms and standards on human rights since Western and Arab values diverge substantially, and these differences are reflected in such instruments. The AHRD suffers from the inspiration of autocratic regimes that promoted it and hence fails to include several key basic rights and fundamental freedoms, including the right to freedom of association. While it served as the inspiration for many similar instruments, the UDHR is still unique and inimitable.